Synthesis of bile acid dimers linked with 1,2,3-triazole ring at C-3, C-11, and C-24 positions - Aher, Nilkanth G.; Pore, VS (Synlett, 2005)
1,3-Dipolar cycloaddition of propargyl ester of a bile acid to an azide group attached at different positions of another bile acid gave three new 1,2,3-triazole-containing dimeric analogues in excellent yields.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; Bile acids; Click chemistry; steroidal dimers